Cover Image, Volume 233, Number 12, December 2018. Issue 12 (12th October 2018) - Chammaa, May; Malysa, Agnes; Redondo, Carlos; Jang, Hyejeong; Chen, Wei; Bepler, Gerold; Fernandez‐Valdivia, Rodrigo
Abstract : Cover : The cover image, by Chammaa et al., is based on Original Research Article, RUMI is a novel negative prognostic marker and therapeutic target in non‐small‐cell lung cancer, DOI: 10.1002/jcp.26858 .